Steel plate
By inhibiting the production of stripe -like hard phases in the steel plate, it promotes the uniform dispersing of the hard phase, and controls the solidarity tissue as a cylindrical crystal, which solves the problem of poor appearance after the formation of high -strength steel plates, and realizes the combination of high strength and excellent appearance.
Patent Information
- Application Number
- CN202380045842.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-30
- Filing Date
- 2023-05-30
- Publication Date
- 2025-01-21
AI Technical Summary
The existing high-strength steel plates are prone to concave and convexity after forming, resulting in poor appearance. Especially in outer plate components, both high strength and excellent design and surface quality are required.
By inhibiting the production of striped hard phases, the uniform dispersing of the hard phase is promoted, the central bias and hard phase rate of the MN are reduced, and the solidarity tissue is controlled as a cylindrical crystal to improve the appearance of the steel plate.
It achieves a significant improvement in the appearance of high-strength steel plates after forming, reduces the generation of ghost lines, and improves the overall performance of the steel plates.
Smart Images

Figure BDA0005177227210000251 
Figure BDA0005177227210000261
Abstract
Description
Technical Field
[0001] The present invention relates to steel sheets. Background Art
[0002] In the automotive industry, the weight reduction of vehicle bodies is required from the perspective of improving fuel efficiency. In order to achieve both weight reduction and collision safety, one of the effective methods is to increase the strength of the steel sheets used. Based on this background, the development of high-strength steel sheets is being promoted.
[0003] In connection with this, Patent Document 1 describes a high-strength hot-dip galvanized steel sheet, characterized in that it is a hot-dip galvanized steel sheet having a hot-dip galvanized layer on the surface of a steel sheet serving as a substrate, wherein the substrate contains, in mass%, C: 0.02-0.20%, Si: 0.7% or less, Mn: 1.5-3.5%, P: 0.10% or less, S: 0.01% or less, Al: 0.1-1.0%, N: 0.010% or less, Cr: 0.03-0.5%, and a surface oxidation index A during annealing defined by the mathematical formula A=400Al / (4Cr+3Si+6Mn) in which the contents of Al, Cr, Si, and Mn are terms of the same sign, is greater than 2.3, and the remainder is composed of Fe and unavoidable impurities, and further, the structure of the substrate is composed of ferrite and a second phase, and the second phase is a phase mainly composed of martensite. Furthermore, Patent Document 1 describes that the high-strength hot-dip galvanized steel sheet has excellent surface quality and a tensile strength of 590 MPa or more, which is suitable for use as structural parts of automobiles such as cross members and swing arms.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2005-220430
[0007] Patent document 2: International Publication No. 2022 / 181761
[0008] Patent Document 3: International Publication No. 2020 / 145256 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In recent years, in conjunction with the demand for further improvement in fuel efficiency, not only the structural components such as the crossbeams described in Patent Document 1 are required to be lightweight, but also the demand for lightweight exterior panel components such as the roof, hood, fenders and doors is increasing. These exterior panel components are different from the structural components described above. Since they are visible to people, not only the characteristics such as strength are important, but also the design and surface quality are important, so excellent appearance after forming is required. On the other hand, in conjunction with such lightweight requirements, the steel plates used in these exterior panel components are also required to be further strengthened and thinned. In addition, as the shapes of these exterior panel components become more complicated, there is a tendency for the surface of the steel plate after forming to become easily uneven, and when such unevenness occurs, there is a problem of reduced appearance.
[0011] More specifically, in the case of DP steel (Dual Phase steel) composed of soft ferrite and a hard second phase mainly composed of martensite, such as described in Patent Document 1, uneven deformation in which the soft phase composed of ferrite and its surroundings are preferentially deformed is likely to occur during processing such as press forming. Therefore, when using such a composite structure steel composed of a soft phase and a hard phase, sometimes fine irregularities are generated on the surface of the steel sheet after forming, resulting in appearance defects called ghost lines.
[0012] As a means of suppressing such unevenness on the surface of a steel plate, for example, Patent Document 3 discloses a steel plate having a specific chemical composition and metal structure, wherein a value X1 obtained by dividing the standard deviation in the thickness direction of the average Mn concentration in the rolling direction at a position 1 / 4 in the thickness direction by the average Mn concentration is 0.025 or less. In addition, Patent Document 4 discloses a steel plate having a specific chemical composition and comprising the following texture: the metal structure of the surface region is composed of ferrite and a second phase having a volume fraction of 0.01 to 5.0%, the metal structure of the inner region is composed of ferrite and a second phase having a volume fraction of 2.0 to 10.0%, the volume fraction of the second phase in the surface region is smaller than the volume fraction of the second phase in the inner region, the average grain size of the second phase in the surface region is 0.01 to 4.0 μm, and the intensity ratio X1 of the {001} orientation to the {111} orientation of ferrite is ODF{001} / {111} It is 0.60 or more and less than 2.00.
[0013] An object of the present invention is to provide a high-strength steel sheet having an improved appearance after forming by a novel structure.
[0014] Means for solving problems
[0015] In order to achieve the above-mentioned purpose, the present inventors have conducted detailed research focusing on the morphology of the hard phase in the metal structure. As a result, the present inventors have found that by suppressing the generation of hard phases connected in stripes (striped hard phases) and making the hard phases in the metal structure more uniformly dispersed, high strength based on such hard phases is maintained, and the appearance defects after forming are improved. Specifically, the present inventors have found that by reducing the central segregation of Mn during solidification, which is the cause of the generation of the striped hard phase, while reducing the hard phase fraction and reducing its unevenness, it is possible to fully maintain high strength and significantly improve the appearance defects after forming.
[0016] The present invention has been accomplished based on these findings, and includes the following aspects.
[0017] (Scheme 1) A steel plate, characterized in that its chemical composition is calculated by mass % as follows:
[0018] C: 0.030~0.100%,
[0019] Mn: 1.00~2.50%,
[0020] Si: 0.005~1.500%,
[0021] P: 0.100% or less,
[0022] S: 0.0200% or less,
[0023] Al: 0.005~0.700%,
[0024] N: 0.0150% or less,
[0025] O: 0.0100% or less,
[0026] Cr: 0~0.80%,
[0027] Mo: 0~0.50%
[0028] B: 0~0.0100%,
[0029] Ti: 0~0.100%,
[0030] Nb: 0~0.100%,
[0031] V: 0~0.50%,
[0032] Ni: 0-1.00%,
[0033] Cu: 0-1.00%,
[0034] W: 0~1.00%,
[0035] Sn: 0~1.00%,
[0036] Sb: 0~0.200%,
[0037] Ca: 0~0.0100%,
[0038] Mg: 0~0.0100%,
[0039] Zr: 0~0.0100%,
[0040] REM: 0~0.0100%, and
[0041] The rest: Fe and impurities,
[0042] Furthermore, the index A represented by the following formula (1) is 0.45% or more;
[0043] The metal structure is calculated by area % as follows: ferrite: 75-97% and hard phase: 3-25%,
[0044] The standard deviation of the hard phase fraction in the direction perpendicular to rolling is less than 0.75%.
[0045] A=[Si]+10[P]+0.6[Al]+8[Ti]+9[Nb] (1)
[0046] Here, [Si], [P], [Al], [Ti], and [Nb] are the contents of the respective elements in mass %, and when the elements are not contained, the content is 0%.
[0047] (Solution 2)
[0048] The steel sheet according to the first aspect is characterized in that the chemical composition contains, in mass %, one or more selected from the group consisting of the following elements:
[0049] Cr: 0.01~0.80%,
[0050] Mo: 0.01~0.50%,
[0051] B: 0.0001~0.0100%,
[0052] Ti: 0.001~0.100%,
[0053] Nb: 0.001~0.100%,
[0054] V: 0.01~0.50%,
[0055] Ni: 0.01~1.00%,
[0056] Cu: 0.01~1.00%,
[0057] W: 0.01~1.00%,
[0058] Sn: 0.01~1.00%,
[0059] Sb: 0.001~0.200%,
[0060] Ca: 0.0001~0.0100%,
[0061] Mg: 0.0001~0.0100%,
[0062] Zr: 0.0001~0.0100%, and
[0063] REM: 0.0001~0.0100%.
[0064] (Solution 3)
[0065] The steel plate according to the above-mentioned aspect 1 or 2 is characterized in that the steel plate satisfies the following formula (2).
[0066] (TS-180,000 / TS) / Vm≥35 (2)
[0067] Here, TS is the tensile strength in MPa, and Vm is the hard phase fraction in area %.
[0068] (Solution 4)
[0069] The steel sheet according to any one of the above-mentioned aspects 1 to 3 is characterized in that the average grain size of the ferrite is 5.0 to 30.0 μm, and the average grain size of the hard phase is 1.0 to 5.0 μm.
[0070] (Scheme 5)
[0071] The steel sheet according to any one of the above aspects 1 to 4 is characterized in that the hard phase is composed of at least one of martensite, bainite, tempered martensite and pearlite.
[0072] Effects of the Invention
[0073] According to the present invention, a high-strength steel sheet having an improved appearance after forming can be provided. DETAILED DESCRIPTION
[0074] Hereinafter, preferred embodiments of the steel sheet of the present invention will be described in detail. In addition, in the present specification, various numerical ranges refer to ranges including the upper and lower limits unless otherwise specified.
[0075] <Steel Plate>
[0076] The steel sheet according to one embodiment of the present invention is characterized in that its chemical composition is expressed in mass % as follows:
[0077] C: 0.030~0.100%,
[0078] Mn: 1.00~2.50%,
[0079] Si: 0.005~1.500%,
[0080] P: 0.100% or less,
[0081] S: 0.0200% or less,
[0082] Al: 0.005~0.700%,
[0083] N: 0.0150% or less,
[0084] O: 0.0100% or less,
[0085] Cr: 0~0.80%,
[0086] Mo: 0~0.50%
[0087] B: 0~0.0100%,
[0088] Ti: 0~0.100%,
[0089] Nb: 0~0.100%,
[0090] V: 0~0.50%,
[0091] Ni: 0-1.00%,
[0092] Cu: 0-1.00%,
[0093] W: 0~1.00%,
[0094] Sn: 0~1.00%,
[0095] Sb: 0~0.200%,
[0096] Ca: 0~0.0100%,
[0097] Mg: 0~0.0100%,
[0098] Zr: 0~0.0100%,
[0099] REM: 0~0.0100%, and
[0100] The rest: Fe and impurities,
[0101] Furthermore, the index A represented by the following formula (1) is 0.45% or more;
[0102] The metal structure is calculated by area % as ferrite: 75-97% and hard phase: 3-25%,
[0103] The standard deviation of the hard phase fraction in the direction perpendicular to rolling is less than 0.75%.
[0104] A=[Si]+10[P]+0.6[Al]+8[Ti]+9[Nb] (1)
[0105] Here, [Si], [P], [Al], [Ti], and [Nb] are the contents of the respective elements in mass %, and when the elements are not contained, the content is 0%.
[0106] In the outer panel parts such as the roof or the door, from the viewpoint of avoiding the surface defects called surface strain generated during press forming, DP steel with relatively low yield strength is often used. However, as mentioned above, in the case of DP steel in which a soft phase composed of ferrite and a hard phase mainly composed of martensite are mixed, it is easy to cause uneven deformation in which the soft phase and its surroundings are deformed preferentially during press forming and other processing. Due to such uneven deformation, tiny bumps and depressions are generated on the surface of the steel sheet after forming, which sometimes produces a poor appearance called ghost lines. If the generation of the ghost lines is explained in more detail, first, during press forming and other processing, the soft phase composed of ferrite is deformed in a concave manner, and on the other hand, the hard phase mainly composed of martensite is not concave or is deformed in a convex manner. As a result, tiny bumps and depressions are formed on the surface of the steel sheet after forming. The tiny bumps and depressions are formed in a manner that the convex portions extending roughly along the rolling direction and the concave portions extending roughly along the rolling direction are arranged in a width direction orthogonal to the rolling direction. Moreover, when the surface of the steel plate after forming is ground, the tiny concave and convex parts of the steel plate surface are cut off, so that the ghost lines of the stripe pattern extending along the rolling direction of the steel plate become obvious. It should be noted that the rolling direction is easily determined based on the extension direction of the grains of the steel plate. In addition, the so-called rolling right-angle direction refers to the direction perpendicular to the rolling direction and the thickness direction.
[0107] Therefore, in order to improve such poor appearance after forming, the present inventors conducted detailed research focusing on the morphology of the hard phase in the metal structure. As a result, the present inventors first found out that in a steel plate such as DP steel where a soft layer and a hard phase are mixed, the degree of ghost lines becomes significant due to the presence of hard phases connected in stripes in the metal structure. In addition, the present inventors found that by suppressing the generation of such stripe-like hard phases and making the hard phases in the metal structure more uniformly dispersed, it is possible to fully maintain high strength and suppress the generation of tiny concavo-convexities on the surface of the steel plate after forming, resulting in the suppression of the generation of ghost lines.
[0108] More specifically, the present inventors have found that, in order to suppress the generation of a stripe-like structure associated with a hard phase, it is effective to reduce the Mn segregation during solidification in a slab casting process in which molten steel is solidified to cast a slab. In this regard, the present inventors have conducted detailed studies on methods for reducing Mn segregation from two viewpoints, namely, central segregation and microsegregation.
[0109] First, the present inventors believed that it is effective to suppress the flow of molten steel during slab casting in order to reduce the central segregation of Mn, and thus conducted various studies. To be described in more detail, the molten steel gradually solidifies from the surface during solidification, and finally solidifies in the center. At this time, since the molten steel gradually discharges the solid phase from the liquid phase, the Mn in the liquid phase gradually becomes concentrated in this stage. If the molten steel flows during solidification, such a concentrated portion of Mn becomes easy to finally concentrate in the center during the solidification process, resulting in a significant central segregation of Mn. Therefore, the present inventors found that when manufacturing steel plates, by appropriately controlling the conditions during solidification to suppress the flow of such molten steel, the central segregation of Mn can be significantly suppressed.
[0110] On the other hand, the present inventors believe that it is effective to promote the diffusion of Mn during solidification in order to reduce the microsegregation of Mn, and thus various studies have been conducted. In order to promote the diffusion of Mn, it is effective to make a structure in which Mn is easy to diffuse. Therefore, the present inventors focus on the δ phase with a fast diffusion rate of Mn, and in order to make the solidification mode become δ solidification, experimentally investigate the influence of each element in the steel on the microsegregation of Mn. As a result, the present inventors found that if the content of C and Mn increases, it will not become δ solidification during solidification, the diffusion rate of Mn decreases and the microsegregation increases, but if the content of Si, Al, Cr and Mo increases, it is possible to promote the diffusion of Mn during solidification and reduce the microsegregation.
[0111] Although ghost lines can be improved by the above-mentioned method of reducing Mn segregation, in order to fully obtain the improvement effect over the entire length and width of the coil, the present inventors have studied a further method of improving ghost lines in addition to studying the above-mentioned method of reducing Mn segregation. As a result, the present inventors first obtained the following understanding: by reducing the hard phase fraction of the steel plate, ghost lines can be improved even if the central segregation of Mn remains to a certain extent. Furthermore, the present inventors obtained the following understanding: the solidification structure also has a great influence on the generation of ghost lines. Even if the central segregation of Mn is small, if coarse equiaxed crystals are generated in the solidification structure, negative segregation of Mn will occur, the unevenness of the hard phase fraction in the rolling right angle direction becomes larger, and the appearance after forming is worsened. Therefore, unlike the previous countermeasures for center segregation (Note: It is common knowledge among those skilled in the art that in order to improve center segregation, the equiaxed crystal fraction needs to be increased. For example, Kawawa Takaho et al.: "Iron and Steel", vol. 60 (1974) No. 5, pp. 486-500, Kumai Hiroshi et al.: "Iron and Steel", Vol. 60 (1974) NO. 7, pp. 894-914), by reducing the equiaxed crystal fraction, the solidification structure is controlled to a columnar crystal structure, thereby suppressing the negative segregation of Mn and improving the ghost line. Based on these insights, the inventors have found that by controlling the solidification structure during casting to a columnar crystal structure, and reducing the cause of the formation of stripe-like hard phases, namely the center segregation of Mn during solidification, while reducing the hard phase fraction and reducing its unevenness, it is possible to fully maintain high strength and significantly improve the poor appearance after forming.
[0112] In one embodiment of the present invention, the steel plate has a specific chemical composition as described above, and has a unique metal structure composed of a lower hard phase fraction than conventional DP steel and with a small variation in the hard phase fraction in a direction perpendicular to rolling. The metal structure can be obtained by adopting a specific chemical composition and casting conditions and controlling the solidification structure during casting to be columnar crystals as described below.
[0113] Since the steel sheet of the present embodiment has such a unique metal structure, that is, a metal structure with small central segregation of Mn during solidification and small hard phase fraction and unevenness, it is possible to sufficiently maintain high strength and suppress the generation of micro-concavities and convexities on the surface of the steel sheet after forming. Therefore, the steel sheet of the present embodiment can sufficiently maintain high strength and significantly suppress the generation of poor appearance after forming such as ghost lines. That is, according to the present embodiment, a high-strength steel sheet with improved appearance after forming can be provided.
[0114] Hereinafter, the steel sheet of the present embodiment will be described in more detail. In the following description, the content of each element and the unit of index A, ie, "%", means "mass %" unless otherwise specified.
[0115] (Chemical Composition)
[0116] The steel sheet of this embodiment has the following specific chemical composition as described above:
[0117] C: 0.030~0.100%,
[0118] Mn: 1.00~2.50%,
[0119] Si: 0.005~1.500%,
[0120] P: 0.100% or less,
[0121] S: 0.0200% or less,
[0122] Al: 0.005~0.700%,
[0123] N: 0.0150% or less,
[0124] O: 0.0100% or less,
[0125] Cr: 0~0.80%,
[0126] Mo: 0~0.50%
[0127] B: 0~0.0100%,
[0128] Ti: 0~0.100%,
[0129] Nb: 0~0.100%,
[0130] V: 0~0.50%,
[0131] Ni: 0-1.00%,
[0132] Cu: 0-1.00%,
[0133] W: 0~1.00%,
[0134] Sn: 0~1.00%,
[0135] Sb: 0~0.200%,
[0136] Ca: 0~0.0100%,
[0137] Mg: 0~0.0100%,
[0138] Zr: 0~0.0100%,
[0139] REM: 0~0.0100%, and
[0140] The rest: Fe and impurities,
[0141] Furthermore, the index A represented by the following formula (1) is 0.45% or more.
[0142] A=[Si]+10[P]+0.6[Al]+8[Ti]+9[Nb] (1)
[0143] Here, [Si], [P], [Al], [Ti], and [Nb] are the contents of the respective elements in mass %, and when the elements are not contained, the content is 0%.
[0144] Hereinafter, each element in the chemical composition will be described in detail.
[0145] [C: 0.030~0.100%]
[0146] C is an element that improves the strength of the steel sheet. In order to fully obtain such an effect, the C content is set to 0.030% or more. The C content may also be 0.035% or more, 0.040% or more, or 0.050% or more. On the other hand, if excessive C is contained, the diffusion of Mn during solidification may be hindered, and the microsegregation of Mn may not be fully suppressed. Therefore, the C content is set to 0.100% or less. The C content may also be 0.095% or less, 0.090% or less, or 0.080% or less.
[0147] [Mn: 1.00~2.50%]
[0148] Mn is an element that improves the hardenability of steel and contributes to the improvement of strength. In order to fully obtain such an effect, the Mn content is set to more than 1.00%. The Mn content can also be more than 1.20%, more than 1.30% or more than 1.40%. On the other hand, if excessive Mn is contained, the diffusion of Mn during solidification may be hindered sometimes, and the microsegregation of Mn cannot be fully suppressed. Therefore, the Mn content is set to less than 2.50%. The Mn content can also be less than 2.25%, less than 2.00% or less than 1.85%.
[0149] [Si: 0.005~1.500%]
[0150] Si is a deoxidizing element for steel and is a solid solution strengthening element effective for improving strength without damaging the ductility of the steel plate. In addition, Si is also an effective element for promoting the diffusion of Mn during solidification and reducing the microsegregation of Mn. In order to fully obtain these effects, the Si content is set to more than 0.005%. The Si content can also be more than 0.010%, more than 0.050% or more than 0.100%. On the other hand, if Si is excessively contained, the peelability of the oxide scale is sometimes reduced and surface defects are generated. Therefore, the Si content is set to less than 1.500%. The Si content can also be less than 1.000%, less than 0.500% or less than 0.300%.
[0151] [P: 0.100% or less]
[0152] P is an element mixed in the manufacturing process. In addition, P is also a solid solution strengthening element. The P content can also be 0%. However, in order to reduce the P content to less than 0.0001%, refining takes time, resulting in a decrease in productivity. Therefore, the P content can also be more than 0.0001%, more than 0.0005%, or more than 0.001%. On the other hand, if P is excessively contained, the toughness of the steel plate sometimes decreases. Therefore, the P content is set to less than 0.100%. The P content can also be less than 0.060%, less than 0.040%, or less than 0.020%.
[0153] [S: 0.0200% or less]
[0154] S is an element mixed in the manufacturing process. The S content may also be 0%. However, in order to reduce the S content to less than 0.0001%, refining takes time, resulting in a decrease in productivity. Therefore, the S content may also be 0.0001% or more, 0.0005% or more, or 0.0010% or more. On the other hand, if S is excessively contained, Mn sulfides may sometimes be formed, which reduces the formability of the steel plate, such as ductility, hole expansion, stretch flangeability and / or bendability. Therefore, the S content is set to 0.0200% or less. The S content may also be 0.0100% or less, 0.0060% or less, or 0.0040% or less.
[0155] [Al: 0.005~0.700%]
[0156] Al is an element that functions as a deoxidizer and is an effective solid solution strengthening element for improving the strength of steel. In addition, Al is also an effective element for promoting the diffusion of Mn during solidification and reducing the microsegregation of Mn. In order to fully obtain these effects, the Al content is set to more than 0.005%. The Al content can also be more than 0.010%, more than 0.020% or more than 0.025%. On the other hand, if Al is excessively contained, castability sometimes deteriorates and productivity decreases. Therefore, the Al content is set to less than 0.700%. The Al content can also be less than 0.600%, less than 0.400%, less than 0.300%, less than 0.200% or less than 0.100%.
[0157] [N: 0.0150% or less]
[0158] N is an element mixed in the manufacturing process. The N content can also be 0%. However, in order to reduce the N content to less than 0.0001%, refining takes time, resulting in a decrease in productivity. Therefore, the N content can also be more than 0.0001%, more than 0.0005%, or more than 0.0010%. On the other hand, if excessive N is contained, nitrides may sometimes be formed, which reduces the formability of the steel plate, such as ductility, hole expansion, stretch flangeability and / or bendability. Therefore, the N content is set to less than 0.0150%. The N content can also be less than 0.0100%, less than 0.0080%, or less than 0.0050%.
[0159] [O: 0.0100% or less]
[0160] O is an element mixed in the manufacturing process. The O content can also be 0%. However, in order to reduce the O content to less than 0.0001%, refining takes time, resulting in a decrease in productivity. Therefore, the O content can also be more than 0.0001%, more than 0.0005%, or more than 0.0010%. On the other hand, if O is excessively contained, coarse oxides are sometimes formed, which reduces the formability of the steel plate, such as ductility, hole expansion, stretch flangeability and / or bendability. Therefore, the O content is set to less than 0.0100%. The O content can also be less than 0.0070%, less than 0.0040%, or less than 0.0020%.
[0161] The basic chemical composition of the steel sheet of the present embodiment is as described above. Furthermore, in the present embodiment, the steel sheet may contain one or more of the following optional elements as needed to replace a part of the remaining Fe. These optional elements are described in detail below.
[0162] [Cr: 0~0.80%]
[0163] Cr is an element that improves the hardenability of steel and contributes to the improvement of the strength of the steel plate. In addition, Cr is also an effective element for promoting the diffusion of Mn during solidification and reducing the microsegregation of Mn. The Cr content can also be 0%, but in order to obtain these effects, the Cr content is preferably 0.001% or more, and more preferably 0.01% or more. The Cr content can also be 0.10% or more, 0.20% or more, or 0.30% or more. On the other hand, if Cr is excessively contained, coarse Cr carbides that become the starting point of fracture are sometimes formed. Therefore, the Cr content is preferably 0.80% or less. The Cr content can also be 0.70% or less, 0.60% or less, or 0.50% or less.
[0164] [Mo: 0 to 0.50%]
[0165] Mo is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of the steel sheet. In addition, Mo is also an effective element for promoting the diffusion of Mn during solidification and reducing the microsegregation of Mn. The Mo content can also be 0%, but in order to obtain these effects, the Mo content is preferably 0.001% or more, and more preferably 0.01% or more. The Mo content can also be 0.05% or more or 0.07% or more. On the other hand, if Mo is excessively contained, hot workability is sometimes reduced and productivity is reduced. Therefore, the Mo content is preferably 0.50% or less. The Mo content can also be 0.40% or less, 0.30% or less, or 0.20% or less.
[0166] [B: 0~0.0100%]
[0167] B is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of the steel sheet. The B content may be 0%, but in order to obtain such an effect, the B content is preferably 0.0001% or more. The B content may also be 0.0005% or more, 0.0010% or more, or 0.0015% or more. On the other hand, if B is excessively contained, B precipitates may be generated, which may reduce the strength of the steel sheet. Therefore, the B content is preferably 0.0100% or less. The B content may also be 0.0080% or less, 0.0060% or less, or 0.0030% or less.
[0168] [Ti: 0~0.100%]
[0169] Ti is an element that has the effect of reducing the amount of S, N and O that are coarse inclusions that act as the starting point of fracture. In addition, Ti is also a precipitation strengthening element that has the effect of refining the structure and improving the strength-formability balance of the steel sheet. The Ti content can also be 0%, but in order to obtain these effects, the Ti content is preferably 0.001% or more. The Ti content can also be 0.005% or more, 0.007% or more, or 0.010% or more. On the other hand, if Ti is excessively contained, coarse Ti sulfides, Ti nitrides and / or Ti oxides are sometimes formed, which reduces the formability of the steel sheet. Therefore, the Ti content is preferably 0.100% or less. The Ti content can also be 0.080% or less, 0.060% or less, or 0.030% or less.
[0170] [Nb: 0~0.100%]
[0171] Nb is a precipitation strengthening element that contributes to the improvement of the strength of the steel sheet due to strengthening caused by precipitates, fine graining strengthening caused by the growth inhibition of ferrite grains, and / or dislocation strengthening caused by the inhibition of recrystallization. The Nb content can also be 0%, but in order to obtain these effects, the Nb content is preferably 0.001% or more. The Nb content can also be 0.005% or more, 0.007% or more, or 0.010% or more. On the other hand, if excessive Nb is contained, sometimes the unrecrystallized ferrite increases and the formability of the steel sheet is reduced. Therefore, the Nb content is preferably 0.100% or less. The Nb content can also be 0.060% or less, 0.040% or less, or 0.030% or less.
[0172] [V: 0~0.50%]
[0173] V is an element that contributes to the improvement of the strength of the steel sheet due to strengthening caused by precipitates, fine graining strengthening caused by the growth inhibition of ferrite grains, and / or dislocation strengthening caused by the inhibition of recrystallization. The V content can also be 0%, but in order to obtain these effects, the V content is preferably 0.001% or more, more preferably 0.005% or more, and further preferably 0.01% or more. The V content can also be 0.02% or more. On the other hand, if V is excessively contained, a large amount of carbonitrides sometimes precipitate and the formability of the steel sheet is reduced. Therefore, the V content is preferably 0.50% or less. The V content can also be 0.40% or less, 0.20% or less, or 0.10% or less.
[0174] [Ni: 0~1.00%]
[0175] Ni is an element that suppresses phase transformation at high temperatures and contributes to the improvement of the strength of the steel sheet. The Ni content may be 0%, but in order to obtain such an effect, the Ni content is preferably 0.001% or more, and more preferably 0.01% or more. The Ni content may also be 0.03% or more or 0.05% or more. On the other hand, if Ni is excessively contained, the weldability of the steel sheet may sometimes be reduced. Therefore, the Ni content is preferably 1.00% or less. The Ni content may also be 0.60% or less, 0.40% or less, or 0.20% or less.
[0176] [Cu: 0-1.00%]
[0177] Cu is an element that exists in steel in the form of fine particles and contributes to the improvement of the strength of the steel plate. The Cu content may be 0%, but in order to obtain such an effect, the Cu content is preferably 0.001% or more, and more preferably 0.01% or more. The Cu content may also be 0.03% or more or 0.05% or more. On the other hand, if Cu is excessively contained, the weldability of the steel plate may be reduced. Therefore, the Cu content is preferably 1.00% or less. The Cu content may also be 0.60% or less, 0.40% or less, or 0.20% or less.
[0178] [W: 0~1.00%]
[0179] W is an element that suppresses phase transformation at high temperatures and contributes to improving the strength of the steel sheet. The W content may be 0%, but in order to obtain such an effect, the W content is preferably 0.001% or more, more preferably 0.01% or more. The W content may also be 0.02% or more or 0.10% or more. On the other hand, if W is excessively contained, hot workability may be reduced and productivity may be reduced. Therefore, the W content is preferably 1.00% or less. The W content may also be 0.80% or less, 0.50% or less, or 0.20% or less.
[0180] [Sn: 0~1.00%]
[0181] Sn is an element that suppresses the coarsening of crystal grains and contributes to the improvement of the strength of the steel sheet. The Sn content may be 0%, but in order to obtain such an effect, the Sn content is preferably 0.001% or more, and more preferably 0.01% or more. The Sn content may also be 0.05% or more or 0.08% or more. On the other hand, excessive Sn may sometimes cause embrittlement of the steel sheet. Therefore, the Sn content is preferably 1.00% or less. The Sn content may also be 0.80% or less, 0.50% or less, or 0.20% or less.
[0182] [Sb: 0~0.200%]
[0183] Sb is an element that suppresses the coarsening of crystal grains and contributes to the improvement of the strength of the steel sheet. The Sb content may be 0%, but in order to obtain such an effect, the Sb content is preferably 0.001% or more. The Sb content may also be 0.01% or more, 0.05% or more, or 0.08% or more. On the other hand, excessive Sn may sometimes cause embrittlement of the steel sheet. Therefore, the Sb content is preferably 1.00% or less, more preferably 0.20% or less. The Sb content may also be 0.10% or less, 0.05% or less, or 0.01% or less.
[0184] [Ca: 0 to 0.0100%], [Mg: 0 to 0.0100%], [Zr: 0 to 0.0100%], and [REM: 0 to 0.0100%]
[0185] Ca, Mg, Zr and REM are elements that contribute to the improvement of the formability of the steel sheet. The content of Ca, Mg, Zr and REM may be 0%, but in order to obtain such an effect, the content of Ca, Mg, Zr and REM is preferably 0.0001% or more. The content of Ca, Mg, Zr and REM may be 0.0005% or more, 0.0010% or more or 0.0015% or more, respectively. On the other hand, if these elements are excessively contained, the ductility of the steel sheet may be reduced. Therefore, the content of Ca, Mg, Zr and REM is preferably 0.0100% or less, respectively. The content of Ca, Mg, Zr and REM may be 0.0080% or less, 0.0060% or less or 0.0030% or less, respectively.
[0186] In this specification, REM is a general term for 17 elements including scandium (Sc) with atomic number 21, yttrium (Y) with atomic number 39, and lanthanide elements from lanthanum (La) with atomic number 57 to lutetium (Lu) with atomic number 71. The REM content is the total content of these elements.
[0187] Regarding the above optional elements, in the present embodiment, the chemical composition of the steel plate preferably contains one or more selected from the group consisting of the following elements:
[0188] Cr: 0.01~0.80%,
[0189] Mo: 0.01~0.50%,
[0190] B: 0.0001~0.0100%,
[0191] Ti: 0.001~0.100%,
[0192] Nb: 0.001~0.100%,
[0193] V: 0.01~0.50%,
[0194] Ni: 0.01~1.00%,
[0195] Cu: 0.01~1.00%,
[0196] W: 0.01~1.00%,
[0197] Sn: 0.01~1.00%,
[0198] Sb: 0.001~0.200%,
[0199] Ca: 0.0001~0.0100%,
[0200] Mg: 0.0001~0.0100%,
[0201] Zr: 0.0001~0.0100%, and
[0202] REM: 0.0001~0.0100%.
[0203] When the steel sheet contains the optional elements as described above, high strength can be more reliably maintained, and the occurrence of appearance defects after forming such as ghost lines can be significantly suppressed.
[0204] In the steel sheet of the present embodiment, the remainder other than the above-mentioned elements is composed of Fe and impurities. Here, the so-called impurities are components mixed in due to various factors in the manufacturing process when the steel sheet is industrially manufactured, such as raw materials such as ore or waste. Examples of impurities include H, Na, Cl, Co, Zn, Ga, Ge, As, Se, Y, Tc, Ru, Rh, Pd, Ag, Cd, In, Te, Cs, Ta, Re, Os, Ir, Pt, Au, Pb, Bi, and Po. The impurities may be contained in a total of 0.100% or less.
[0205] [Index A: 0.45% or more]
[0206] In the present embodiment, the chemical composition of the steel sheet has an index A represented by the following formula (1) of 0.45% or more.
[0207] A=[Si]+10[P]+0.6[Al]+8[Ti]+9[Nb] (1)
[0208] Here, [Si], [P], [Al], [Ti], and [Nb] are the contents of the respective elements in mass %, and when the elements are not contained, the amount is 0%.
[0209] Index A is an index determined by the contents of Si, P and Al as solid solution strengthening elements and Ti and Nb as precipitation strengthening elements. The larger the value, the higher the hard phase fraction can be. By setting index A to 0.45% or more, the hard phase fraction of the steel plate can be controlled to a certain level or less, and high strength can be obtained.
[0210] The index A may be 0.48% or more, 0.50% or more, or 0.52% or more. The upper limit of the index A is not particularly limited, but for example, the index A may be 1.50% or less, 1.20% or less, or 1.00% or less.
[0211] Here, the chemical composition of the steel plate can be measured by a common analysis method. For example, the chemical composition of the steel plate can be measured by inductively coupled plasma emission spectrometry (ICP-AES). C and S can be measured by combustion-infrared absorption method, N can be measured by inert gas fusion-thermal conductivity method, and O can be measured by inert gas fusion-non-dispersive infrared absorption method.
[0212] (Metallic Structure)
[0213] [Ferrite: 75-97% and hard phase: 3-25%]
[0214] In the present embodiment, the metal structure of the steel plate is composed of 75-97% ferrite and 3-25% hard phase in terms of area %. By setting the metal structure of the steel plate to such a composite structure, the strength of the steel plate can be maintained within an appropriate range, more specifically, a tensile strength of 500 MPa or more is achieved, and the appearance after forming is poor. From the perspective of further improving the strength of the steel plate, the area fraction of the hard phase can also be 7% or more, 10% or more, 12% or more, or 15% or more. Similarly, the area fraction of ferrite can also be 93% or less, 90% or less, 88% or less, or 85% or less. On the other hand, from the perspective of further improving the appearance after forming, the area fraction of the hard phase can also be 24% or less, 22% or less, or 20% or less. Similarly, the area fraction of ferrite can also be 76% or more, 78% or more, or 80% or more.
[0215] In the steel sheet of the present embodiment, the hard phase refers to a structure harder than ferrite, for example, composed of at least one of martensite, bainite, tempered martensite and pearlite. From the viewpoint of improving the strength of the steel sheet, the hard phase is preferably composed of at least one of martensite, bainite and tempered martensite, and more preferably composed of martensite. In the present embodiment, in the metal structure of the steel sheet, the retained austenite is preferably small, and specifically, the retained austenite is preferably less than 1% or less than 0.5% in terms of area %, and more preferably 0%.
[0216] (Identification of metal structure and calculation of area fraction)
[0217] The identification of the metal structure and the calculation of the area fraction are performed as follows. First, a sample for observing the metal structure (microstructure) is collected from the W / 4 position or 3W / 4 position of the plate width W of the obtained steel plate (i.e., a position W / 4 away from any width direction end of the steel plate in the width direction). The size is, for example, 20 mm in the rolling direction × 20 mm in the width direction × the thickness of the steel plate. Then, the metal structure (microstructure) is observed using a scanning electron microscope (SEM). At this time, regarding the observation field, the following 10 fields of view were observed at the positions in the thickness direction of the steel plate: (i) a field of view with a position of 125 μm from the surface of the steel plate (the surface other than the coating layer in the case of the presence of the coating layer) (hereinafter referred to as the "125 μm plate thickness position") as the center of the thickness direction, (ii) a field of view with a position of 1 / 2 plate thickness from the surface of the steel plate (hereinafter referred to as the "1 / 2 plate thickness position") as the center of the thickness direction, (iii) between the above (i) and (ii), 8 fields of view divided into 9 equal intervals from the 125 μm plate thickness position to the 1 / 2 plate thickness position. As a sample adjustment, the plate thickness section in the rolling right angle direction was ground as the observation surface and etched using nitric acid. Next, the "microstructure" was classified according to the SEM photographs with a magnification of 500 or 1000 times. Ferrite and hard phase can be distinguished by the difference in brightness.
[0218] For the steel plate corroded by nitric acid, the observation fields of the above 10 locations were observed at a magnification of 500 times or 1000 times, and the image analysis software "Photoshop (registered trademark) CS5" manufactured by Adobe was used to perform image analysis to determine the area fraction of the hard phase. Ferrite and the hard phase were binarized by the difference in brightness, and the area fraction of the hard phase was calculated. For the observation fields of a total of 10 locations, image analysis was performed in the same manner as above to determine the area fraction of the hard phase, and the area fractions were averaged to calculate the average value. The average value was taken as the area fraction of the hard phase, and the remainder was taken as the area fraction of ferrite. It should be noted that the observation area of each field of view was set to 150 μm in the plate thickness direction and 250 μm in the rolling direction (the observation area in this case is 150×250=37500 μm). 2 ).
[0219] Furthermore, when it is necessary to measure the area fraction of retained austenite, the area fraction of retained austenite can be measured by X-ray diffraction of the above-mentioned observation surface. Specifically, using Co-Kα rays, the integrated intensity of a total of six peaks of α(110), α(200), α(211), γ(111), γ(200), and γ(220) at the 1 / 4 position in the plate thickness direction is obtained, and the volume fraction of retained austenite is calculated using the intensity average method, and the obtained volume fraction of retained austenite is used as the area fraction of retained austenite.
[0220] [Standard deviation of the hard phase fraction in the direction perpendicular to rolling: 0.75% or less]
[0221] In the present embodiment, the standard deviation of the hard phase fraction of the metal structure of the steel plate in the direction perpendicular to the rolling is less than 0.75%. It should be noted that the standard deviation of the hard phase fraction refers to the standard deviation of the area fraction of the hard phase itself. As mentioned above, for the poor appearance after forming such as ghost lines, not only the influence of Mn segregation is greatly related, but also the influence of the solidification structure is greatly related. For example, even if the central segregation of Mn is small, if coarse equiaxed crystals are generated in the solidification structure, negative segregation of Mn may sometimes occur, the unevenness of the hard phase fraction in the direction perpendicular to the rolling becomes larger, and the poor appearance after forming worsens. However, in the steel plate of the present embodiment, since the standard deviation of the hard phase fraction in the direction perpendicular to the rolling is less than 0.75%, that is, the unevenness of the hard phase fraction in the direction perpendicular to the rolling is less than a certain level, the poor appearance after forming can be significantly suppressed. It should be noted that, for the hard phase fraction, the ratio of the average value of the area ratio of the hard phase to its standard deviation is preferably 0.10 or less (i.e., standard deviation of the hard phase fraction / average value of the area ratio of the hard phase ≤ 0.10). The above ratio is preferably 0.09 or less, 0.08 or less, or 0.07 or less. The lower limit of the above ratio is 0, but as required, the lower limit may also be set to 0.01.
[0222] The standard deviation of the hard phase fraction in the rolling right angle direction of the metal structure can be calculated as follows. First, the range between a position 50 μm from one surface of the steel plate and a position 50 μm from the other surface of the steel plate of a cross section parallel to the rolling right angle direction of the steel plate and perpendicular to the surface of the steel plate is observed with a scanning electron microscope (SEM) at a magnification of 500 times or 1000 times to obtain a SEM photo image. For the SEM photo image, the image analysis software is used to analyze the image in the same way as the area fraction of the hard phase described above, and the area fraction of the hard phase per 100 μm within the range of 8 mm in the rolling right angle direction of the steel plate is measured, and its standard deviation is calculated. It should be noted that the observation range in the rolling right angle direction can also be less than 8 mm or more than 8 mm. However, the lower limit of the observation range of the standard deviation of the hard phase fraction in the rolling right angle direction is set to 4 mm, and the upper limit is set to 12 mm.
[0223] From the viewpoint of further improving the appearance after forming, the standard deviation of the hard phase fraction in the direction perpendicular to rolling may also be 0.65% or less, 0.55% or less, or 0.45% or less. It should be noted that the lower limit of the standard deviation is not particularly limited, but for example, the standard deviation of the hard phase fraction may also be 0.01% or more, 0.05% or more, 0.10% or more, 0.15% or more, or 0.20% or more.
[0224] [Relationship between the tensile strength of steel plate and the hard phase fraction: (TS-180,000 / TS) / Vm≥35]
[0225] In the present embodiment, the steel plate preferably satisfies the following formula (2).
[0226] (TS-180,000 / TS) / Vm≥35 (2)
[0227] Here, TS represents tensile strength (MPa), and Vm represents hard phase fraction (area %).
[0228] If the steel sheet satisfies the formula (2), even if a certain degree of central segregation of Mn remains, it is easy to suppress the unevenness of the hard phase fraction in the direction perpendicular to rolling, and as a result, it is easier to prevent appearance defects of the steel sheet after forming.
[0229] The tensile strength (TS) of the steel plate can be measured by taking a No. 5 tensile test piece of JIS Z2241:2011 from the steel plate with the longitudinal direction being perpendicular to the rolling direction, and performing a tensile test in accordance with JIS Z2241:2011.
[0230] [Average grain size of ferrite: 5.0 to 30.0 μm]
[0231] In the steel plate of the present embodiment, the average crystal grain size of ferrite in the metal structure is preferably 5.0 to 30.0 μm. If the average crystal grain size of ferrite is controlled within such a fine range, the appearance of the steel plate after forming can be further improved. The average crystal grain size of ferrite can also be 7.0 μm or more, 8.0 μm or more, 9.0 μm or more, or 10.0 μm or more. Similarly, the average crystal grain size of ferrite can also be 27.0 μm or less, 25.0 μm or less, 20.0 μm or less, or 16.0 μm or less.
[0232] The average crystal grain size of ferrite in the steel plate is determined as follows. First, in the area from the surface to the position of 1 / 2 of the plate thickness in the plate thickness direction of the steel plate after corrosion using nital, 10 fields of view in the same plate thickness direction as the above-mentioned determination of the area fraction of ferrite and hard phase are observed at a magnification of 500 times, and the image analysis software "Photoshop (registered trademark) CS5" manufactured by Adobe Company is used to perform image analysis, and the area fraction of ferrite and the number of ferrite particles in each field of view are calculated respectively. Next, the area fraction of ferrite and the number of ferrite particles in the 10 fields of view are respectively totaled, and the average area fraction of each ferrite particle is calculated by dividing the total area fraction of ferrite by the total number of ferrite particles. The equivalent circle diameter is calculated from the average area fraction and the number of particles, and the obtained equivalent circle diameter is determined as the average crystal grain size of ferrite. It should be noted that the observation area of each field of view is set to 150 μm in the plate thickness direction and 250 μm in the rolling direction (the observation area in this case is 150×250=37500 μm). 2 ).
[0233] [Average grain size of hard phase: 1.0 to 5.0 μm]
[0234] In the steel plate of the present embodiment, the average crystal grain size of the hard phase in the metal structure is preferably 1.0 to 5.0 μm. If the average crystal grain size of the hard phase is controlled within such a fine range, the appearance of the steel plate after forming can be further improved. The average crystal grain size of the hard phase can also be greater than 1.2 μm, greater than 1.5 μm, greater than 1.7 μm, or greater than 2.0 μm. Similarly, the average crystal grain size of the hard phase can also be less than 4.7 μm, less than 4.5 μm, less than 4.2 μm, or less than 4.0 μm.
[0235] The average crystal grain size of the hard phase is determined as follows. First, in the area from the surface to the position of 1 / 2 of the thickness in the thickness direction of the steel plate after corrosion using nital, 10 fields of view in the same thickness direction as the above-mentioned determination of the area fraction of ferrite and hard phase are observed at a magnification of 500 times, and the image analysis software "Photoshop (registered trademark) CS5" manufactured by Adobe Company is used for image analysis, and the area fraction of the hard phase and the number of particles of the hard phase in each field of view are calculated respectively. Then, the area fraction of the hard phase and the number of particles of the ferrite in the 10 fields of view are respectively totaled, and the average area fraction of each hard phase particle is calculated by dividing the total area fraction of the hard phase by the total number of particles of the hard phase. The equivalent circle diameter is calculated from the average area fraction and the number of particles, and the obtained equivalent circle diameter is determined as the average crystal grain size of the hard phase. It should be noted that the observation area of each field of view is set to 150 μm in the plate thickness direction and 250 μm in the rolling direction (the observation area in this case is 150×250=37500 μm). 2 ).
[0236] (plate thickness)
[0237] In the present embodiment, the thickness of the steel plate is not particularly limited, but for example, the steel plate may have a thickness of 0.1 to 2.0 mm. A steel plate having such a thickness is suitable when used as a raw material for a cover member such as a door or an engine hood. It should be noted that the thickness of the steel plate may be greater than 0.2 mm, greater than 0.3 mm, or greater than 0.4 mm. Similarly, the thickness of the steel plate may be less than 1.8 mm, less than 1.5 mm, less than 1.2 mm, or less than 1.0 mm. For example, by setting the thickness of the steel plate to more than 0.2 mm, it becomes easy to maintain the shape of the formed product flat, and additional effects such as improved dimensional accuracy and shape accuracy can be obtained. On the other hand, by setting the thickness to less than 1.0 mm, the lightweight effect of the component becomes significant. The thickness of the steel plate is measured by a micrometer.
[0238] (Plating)
[0239] For the purpose of improving corrosion resistance, the steel sheet of the present embodiment may further include a coating on the surface. The coating may be any one of a hot-dip coating and an electroplated coating. As a hot-dip coating, for example, a hot-dip galvanized layer (GI), an alloyed hot-dip galvanized layer (GA), a hot-dip aluminum coating, a hot-dip Zn-Al alloy coating, a hot-dip Zn-Al-Mg alloy coating, a hot-dip Zn-Al-Mg-Si alloy coating, etc. may be listed. As an electroplated coating, for example, an electrogalvanized layer (EG), an electroplated Zn-Ni alloy coating, etc. may be listed. Among them, the coating is preferably a hot-dip galvanized layer, an alloyed hot-dip galvanized layer or an electrogalvanized layer. The amount of coating adhesion is not particularly limited and may be a common amount of adhesion.
[0240] (Mechanical properties)
[0241] According to the steel plate of this embodiment having the above-mentioned specific chemical composition and metal structure, a high tensile strength, specifically a tensile strength of 500 MPa or more, can be achieved. The tensile strength of the steel plate is preferably 540 MPa or more, and more preferably 600 MPa or more. The upper limit of the tensile strength is not particularly limited, but for example, the tensile strength may be 980 MPa or less or 850 MPa or less. By setting the tensile strength to 850 MPa or less, there is an advantage that it is easy to ensure the formability of the steel plate when it is pressed.
[0242] The steel sheet of this embodiment has high strength, specifically, a tensile strength of 500 MPa or more, but can maintain an excellent appearance even after forming by press working, etc. Therefore, the steel sheet of this embodiment is very useful for use as outer panel parts such as roofs, hoods, fenders, and doors that require high design in automobiles.
[0243] <Method for manufacturing steel sheet>
[0244] Next, a preferred method for manufacturing a steel plate according to an embodiment of the present invention will be described. The following description is intended to illustrate a characteristic method for manufacturing a steel plate according to an embodiment of the present invention, and is not intended to limit the steel plate to a steel plate manufactured by the manufacturing method described below.
[0245] The method for manufacturing a steel plate of the present embodiment includes a casting step of casting a slab having the above-mentioned specific chemical composition. The casting step includes: performing light reduction using a continuous casting machine having a plurality of adjacent reduction rolls in the conveying direction of the slab, and the roller spacing between adjacent reduction rolls is 290 mm or less. It should be noted that in this specification, the so-called light reduction refers to a reduction with a reduction gradient of 0.6 mm or more per 1 m in the casting forward direction.
[0246] (Casting process)
[0247] As described above, the steel plate of the present embodiment is indispensable to have a unique metal structure including a lower hard phase fraction than the conventional DP steel and a small nonuniformity of the hard phase fraction in the direction perpendicular to rolling. In order to obtain such a metal structure, it is important to control the solidification structure during casting in a columnar crystal. Specifically, in the casting process, by setting the superheat ΔT (the difference between the molten steel temperature and the solidification temperature of the molten steel) of the molten steel having the above-mentioned specific chemical composition to 25°C or more, and further setting the section pressing force to 450 tons or more, the center segregation can be suppressed despite the use of a method different from the conventional center segregation countermeasure of controlling the solidification structure to a columnar crystal structure with an equiaxed crystal ratio of less than 15%. The superheat ΔT is more preferably 30°C or more. In addition, the superheat ΔT is preferably 40°C or less. It should be noted that the molten steel temperature is the temperature of the molten steel in the tundish, which can be obtained by actual measurement. The solidification temperature can be obtained from the chemical composition of the molten steel using a known solidification temperature estimation formula.
[0248] It should be noted that the conventional countermeasure for improving center segregation is to minimize the overheat ΔT (at least set it to less than 25°C) and increase the equiaxed crystal ratio (at least increase it to more than 15%), but such conventional countermeasures cannot achieve sufficient improvement effects. In this embodiment, by adopting casting conditions that are completely different from the conventional countermeasures, that is, setting the overheat ΔT to more than 25°C and setting the segment pressing force to more than 450 tons, the solidification structure is controlled to be a columnar crystal structure, and the negative segregation of Mn can be suppressed. As a result, the microsegregation of Mn is reduced, and the ghost line can be sufficiently improved.
[0249] The equiaxed crystal ratio (%) can be calculated by the following method: collect the etching print of the thickness section of the slab in the width direction and determine the boundary between the columnar crystal structure and the equiaxed crystal structure by visual observation, measure the thickness (mm) of the equiaxed crystal structure at the center of the thickness of the slab and the thickness (mm) of the slab, divide the thickness of the equiaxed crystal structure by the thickness of the slab and multiply by 100.
[0250] In addition, in the casting process, by using a continuous casting machine with a roll spacing of 290 mm or less between adjacent multiple reduction rolls to implement soft reduction, the flow of molten steel during solidification can be suppressed, and the concentration of Mn in the center can be reduced. Thus, the center segregation of Mn can be suppressed. It should be noted that the roll spacing of the adjacent multiple reduction rolls is more preferably 280 mm or less.
[0251] The method for manufacturing the steel plate of the present embodiment may include other processes such as a hot rolling process, a cold rolling process, an annealing process, and a cooling process in addition to the above-mentioned casting process. Furthermore, the present manufacturing method may optionally include a plating process. These processes are not particularly limited, and any suitable conditions may be appropriately selected to implement them in a manner that a metal structure containing the above-mentioned ferrite and hard phase at a prescribed area fraction associated with the steel plate can be obtained. Below, for these processes, preferred conditions are briefly described.
[0252] (Hot rolling process)
[0253] Before hot rolling, the slab is preferably heated to 1100°C or higher. By setting the heating temperature to 1100°C or higher, the rolling reaction force will not become too large during hot rolling, and the target product thickness can be easily obtained. The upper limit of the heating temperature is not particularly limited, but from an economic point of view, the heating temperature is preferably set to less than 1300°C. In the hot rolling process, the heated slab is subjected to rough rolling and finish rolling. The hot-rolled steel sheet obtained in this way is coiled at a coiling temperature of 450 to 650°C, for example.
[0254] It should be noted that the finishing temperature of the finishing rolling is preferably set to 950°C or less. By setting the finishing temperature of the finishing rolling to 950°C or less, the average grain size of the hot-rolled steel sheet and the final product can be reduced, and sufficient yield strength and high surface quality after forming can be ensured. In addition, by setting the coiling temperature to 450-650°C, the average grain size can be reduced and the growth of oxide scale can be suppressed.
[0255] (Cold rolling process)
[0256] The hot-rolled steel sheet obtained by the hot rolling process is subjected to a cold rolling process after being subjected to a pickling treatment to remove oxide scale. In the cold rolling process, the hot-rolled steel sheet is preferably cold-rolled in such a manner that the cumulative reduction ratio is 50 to 90%. By controlling the cumulative reduction ratio to such a range, the desired plate thickness can be ensured, the uniformity of the material in the plate width direction can be fully ensured, and the rolling load can be prevented from becoming too large and making rolling difficult.
[0257] (Annealing process)
[0258] In the annealing process, it is preferred to perform an annealing treatment in which the cold-rolled steel sheet is heated to an absorptive temperature of 750 to 900°C and maintained. By setting the absorptive temperature to 750°C or higher, the recrystallization of ferrite and the reverse transformation from ferrite to austenite can be fully performed, and the desired metal structure can be obtained in the final product. On the other hand, by setting the absorptive temperature to 900°C or lower, the grains can be densified and sufficient strength can be obtained.
[0259] (Cooling process)
[0260] In the cooling process, the cold-rolled steel sheet after the annealing process is cooled. In the cooling process, the cold-rolled steel sheet is preferably cooled in such a manner that the average cooling rate from the soaking temperature is 5 to 50°C / second. By setting the average cooling rate to be above 5°C / second, it is possible to suppress excessive phase transformation to ferrite, and increase the amount of hard phases such as martensite to obtain the desired strength. In addition, by setting the average cooling rate to be below 50°C / second, the steel sheet can be cooled more uniformly in the width direction.
[0261] (Plating process)
[0262] For the purpose of improving corrosion resistance, the surface of the obtained cold-rolled steel sheet may also be subjected to a plating treatment. Examples of plating treatments include hot-dip plating, alloying hot-dip plating, and electroplating. For example, as a plating treatment, a hot-dip galvanizing treatment may be applied to the surface of the steel sheet, or an alloying treatment may be applied after the hot-dip galvanizing treatment. The specific conditions for the plating treatment and the alloying treatment are not particularly limited, and any suitable conditions known to those skilled in the art may be adopted. For example, the alloying temperature may also be 450 to 600°C.
[0263] It should be noted that the present invention is not limited to the above-mentioned embodiment, the following examples, etc., and appropriate combinations, substitutions, changes, etc. can be made without departing from the purpose and spirit of the present invention.
[0264] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.
[0265] Example
[0266] In the following examples, a steel sheet according to an embodiment of the present invention was produced under various conditions, and the tensile strength, post-forming appearance characteristics, and the like of the obtained steel sheets were examined.
[0267] First, a continuous casting machine having a plurality of reduction rolls arranged at a roll pitch of less than 290 mm was used to cast a slab having the chemical composition shown in Table 1 and a thickness of 200 to 300 mm by implementing a continuous casting method with a light reduction with a reduction gradient of more than 0.6 mm per 1 m in the casting forward direction. The remainder other than the components shown in Table 1 is Fe and impurities. In each example, the casting condition (I) is a condition of overheating ΔT ≥ 25°C, and the casting condition (II) is a condition of a zone pressing force ≥ 450 tons. In each example, the conditions that satisfy each of these conditions (recorded as "OK") and the conditions that do not satisfy them (recorded as "NG") are shown in Table 2.
[0268] Next, the obtained slab was subjected to a hot rolling process (heating temperature 1200°C, finishing temperature 900°C and coiling temperature 550°C), a cold rolling process (cumulative reduction rate 80%), an annealing process (soaking temperature 800°C) and a cooling process (average cooling rate 10°C / second) to produce a cold-rolled steel sheet with a thickness of 0.4 mm. The surface of the obtained cold-rolled steel sheet was suitably plated to form a hot-dip galvanized layer (GI), an alloyed hot-dip galvanized layer (GA) or an electroplated galvanized layer (EG). In addition, the chemical composition of the sample collected from the manufactured cold-rolled steel sheet was analyzed, and the result was no change compared with the chemical composition of the slab shown in Table 1.
[0269]
[0270]
[0271] The properties of the obtained steel sheets were measured and evaluated by the following methods.
[0272] (tensile strength)
[0273] The tensile strength of the steel plate was measured by taking a No. 5 tensile test piece of JIS Z2241:2011 from the steel plate with the longitudinal direction being perpendicular to the rolling direction, and performing a tensile test in accordance with JIS Z2241:2011.
[0274] Furthermore, using the measured tensile strength of the steel sheet, the relationship between the tensile strength (TS) of the steel sheet and the hard phase fraction (Vm): (TS-180,000 / TS) / Vm was calculated.
[0275] (Appearance after forming)
[0276] The appearance of the steel sheet after forming is evaluated by the degree of ghost lines generated on the surface of the formed door outer panel. The surface after press forming is polished with a grinding wheel, and the stripe pattern generated on the surface with a few mm interval is judged as ghost lines. Based on the following criteria according to the degree of generation of the stripe pattern, the score is scored with a score of 1 to 5. By visually confirming an arbitrary area of 100mm×100mm, the case where no stripe pattern is confirmed at all is set as "1", the case where the maximum length of the stripe pattern is less than 20mm is set as "2", the case where the maximum length of the stripe pattern exceeds 20mm and is less than 50mm is set as "3", the case where the maximum length of the stripe pattern exceeds 50mm and is less than 70mm is set as "4", and the case where the maximum length of the stripe pattern exceeds 70mm is set as "5". The case evaluated as "3" or less is set as excellent appearance after forming and is judged as qualified. On the other hand, the case evaluated as "4" or more is set as poor appearance after forming and is judged as unqualified.
[0277] The steel sheets having a tensile strength of 500 MPa or more and an appearance evaluation after forming of 3 or less were evaluated as high-strength steel sheets having improved appearance after forming.
[0278] Referring to Table 2, the steel sheets No. 3, 4, 12, 16, 17, and 23 to 27, whose standard deviations of the hard phase fraction of the chemical composition or the metal structure are outside the range of the present invention, all have poor appearance after forming. In addition, the steel sheet No. 28, whose chemical composition and the ferrite fraction and the hard phase fraction of the metal structure are outside the range of the present invention, has a good appearance after forming, but the hard phase fraction is low due to the low C content, and sufficient strength is not obtained.
[0279] On the other hand, the examples of the present invention of steel plates No. 1, 2, 5 to 11, 13 to 15, and 18 to 22 can maintain a high strength of more than 500 MPa in tensile strength, and even when strain is imparted by press forming, the generation of tiny irregularities on the surface of the steel plates can be suppressed and the generation of ghost lines can be significantly suppressed.
Claims
1. A steel plate, characterized in that: Its chemical composition in mass % is: C:0.030~0.100%、 Mn: 1.00~2.50%, Si: 0.005~1.500%, P: 0.100% or less, S: 0.0200% or less, Al:0.005~0.700%、 N: 0.0150% or less, O: 0.0100% or less, Cr:0~0.80%、 Mo: 0~0.50% B:0~0.0100%、 Ti: 0~0.100%, Nb: 0~0.100%, V:0~0.50%、 Ni: 0-1.00%, Cu: 0-1.00%, W:0~1.00%、 Sn: 0~1.00%, Sb: 0~0.200%, Ca: 0~0.0100%, Mg: 0~0.0100%, Zr:0~0.0100%、 REM: 0~0.0100%, and The rest: Fe and impurities, Furthermore, the index A represented by the following formula (1) is 0.45% or more; The metal structure is calculated by area % as follows: ferrite: 75-97% and hard phase: 3-25%, and the standard deviation of the hard phase fraction in the direction perpendicular to rolling is less than 0.75%, A=[Si]+10[P]+0.6[Al]+8[Ti]+9[Nb] (1) Here, [Si], [P], [Al], [Ti], and [Nb] are the contents of the respective elements in mass %, and when the elements are not contained, the amount is 0%.
2. The steel plate according to claim 1, characterized in that: The chemical composition contains, in mass %, one or more selected from the group consisting of the following elements: Cr:0.01~0.80%、 Mo: 0.01~0.50%, B:0.0001~0.0100%、 Ti: 0.001~0.100%, Nb: 0.001~0.100%, V:0.01~0.50%、 Ni: 0.01~1.00%, Cu: 0.01~1.00%, W:0.01~1.00%、 Sn: 0.01~1.00%, Sb: 0.001~0.200%, Ca: 0.0001~0.0100%, Mg: 0.0001~0.0100%, Zr: 0.0001~0.0100%, and REM: 0.0001~0.0100%.
3. The steel plate according to claim 1 or 2, characterized in that: The steel plate satisfies the following formula (2): (TS-180,000 / TS) / Vm≥35 (2) Here, TS is the tensile strength in MPa, and Vm is the hard phase fraction in area %.
4. The steel plate according to any one of claims 1 to 3, characterized in that The average grain size of the ferrite is 5.0 to 30.0 μm, and the average grain size of the hard phase is 1.0 to 5.0 μm.
5. The steel plate according to any one of claims 1 to 4, characterized in that: The hard phase is composed of at least one of martensite, bainite, tempered martensite and pearlite.
Citation Information
Patent Citations
High strength hot dip galvanized steel sheet having excellent surface quality
JP2005220430A
Steel sheet and method for manufacturing same
WO2020145256A1
Steel sheet
WO2022181761A1